Conflict in modern Japanese history : (Princeton University Press, 1982)
This volume depicts the conflict and uncertainty that have bedeviled modern Japan. The eighteen contributors explore dissent, secession, and conflict first in the 1850s and 1860s, when the Tokugawa regime gave way to the Meiji government, and then from the end of the Russo-Japanese War through the mid-1920s.